The production of isolated photons in PbPb and pp collisions at √sNN = 5.02 TeV; Journal of High Energy Physics; Vol. 2020, iss. 7 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer Th. Thomas; Zhokin A. S. Aleksandr Sergeevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2020, 2020)
Title screen